Characteristics and Determinants Of Precarious Employment In Indonesia - Oni Prasetyo Utomo; Lilik Sugiharti (Trunojoyo University of Madura, 2022)
Precarious employment is indicator of non-standard work that describes workers in a vulnerable position to lose their jobs which can lead to poverty and can hinder sustainable development. The rapid growth of precarious employment rate is a serious challenge for a developing country. This study aims to analyze the factors that affect precarious workers in Indonesia. The data used in this study is Sakernas August 2019. The analytical method used in this study is logistic regression, where the independent variables are the demographic and employment characteristics of individuals along with macro conditions of regional employment. The findings of this study are that young workers, male, low-educated, unmarried status, and living in urban areas, tend to be precarious workers. Those who work in the manufacturing industry and less than one year of work experience are more likely to become precarious workers. High unemployment rates and low regional average wages also put individuals at greater risk of becoming precarious workers.